Insectos acuáticos y calidad del agua en la cuenca y embalse del río Peñas Blancas, Costa Rica - Guevara Mora, Meyer (Universidad de Costa Rica, 2011)
The aquatic insects have been used to evaluate water quality of aquatic environments.The population of aquatic insects and the water quality of the area were characterized according to the natural and human alterations present in the study site. During the monthly-survey, pH, DO, temperature, water level, DBO, PO4 and NO3 were measured. Biological indexes (abundance, species richness and the BMWP-CR) were used to evaluate the water quality. No relation between environmental and aquatic insects was detected. Temporal and spatial differences attributed to the flow events (temporal) and the presence of Peñas Blancas reservoir (spatial). In the future, the investigations in Peñas Blancas watershed need to be focused on determining the real influence of the flows, sediment release and the possible water quality degradation because of agriculture activities.